The Modernizing Process in Turkey: Sociological Views - Öztürk, Hatice Karakus (Nomos Verlagsgesellschaft mbH & Co. KG, 2018)
This book is about the continuity and historical and sociological ruptures experienced by Turkey during its process of modernisation. The author’s aim is to reveal Turkey’s social structure through theoretical and empirical examinations and by using certain problems as a point of reference.The topics she discusses are gender, space, borders and immigration, urbanity, economic activities, Turkey’s social fabric, citizenship, childhood, family, and the transformations in the country’s politics and culture.Dr. Hatice Karakuş Öztürk has written studies on fields such as childhood, bullying, and the sociology of the family and gender. She lives in Hopa, Artvin, where she is a faculty member of the department of sociology at Artvin Çoruh University.